Orchidaceae Americanae Orchidaceae Americanae - Jones H. G. (Caldasia)
The following paper continues the series of nomenclatural notes and adjustments commenced under the title "Studies in Neotropical Orchidology" in Acta Botanica Academiae Scientiarum Hungaricae, Vol. 14: pp. 63-70 (1968). As in the previous contribution, the genera considered in the present study are Brassavola R. Br., Schomburgkia Lindl, and Hoffmannseggella H. G. Jones. The notes which comprise this series of studies have been accumulated during the course of collecting materials for a taxonomic revision of the three genera concerned. The following paper continues the series of nomenclatural notes and adjustments commenced under the title "Studies in Neotropical Orchidology" in Acta Botanica Academiae Scientiarum Hungaricae, Vol. 14: pp. 63-70 (1968). As in the previous contribution, the genera considered in the present study are Brassavola R. Br., Schomburgkia Lindl, and Hoffmannseggella H. G. Jones. The notes which comprise this series of studies have been accumulated during the course of collecting materials for a taxonomic revision of the three genera concerned.